Associations of CSF PDGFRβ With Aging, Blood-Brain Barrier Damage, Neuroinflammation, and Alzheimer Disease Pathologic Changes - Cicognola, Claudia; Mattsson-Carlgren, Niklas; van Westen, Danielle; Zetterberg, Henrik; Blennow, Kaj; Palmqvist, Sebastian; Ahmadi, Khazar; Strandberg, Olof; Stomrud, Erik; Janelidze, Shorena; Hansson, Oskar (Neurology, 2023)
Injured pericytes in the neurovascular unit release platelet-derived growth factor β (PDGFRβ) into the CSF. However, it is not clear how pericyte injury contributes to Alzheimer disease (AD)-related changes and blood-brain barrier (BBB) damage. We aimed to test whether CSF PDGFRβ was associated with different AD-associated and age-associated pathologic changes leading to dementia. PDGFRβ was measured in the CSF of 771 participants with cognitively unimpaired (CU, n = 408), mild cognitive impairment (MCI, n = 175), and dementia (n = 188) from the Swedish BioFINDER-2 cohort. We then checked association with β-amyloid (Aβ)-PET and tau-PET standardized uptake value ratio, ε4 genotype and MRI measurements of cortical thickness, white matter lesions (WMLs), and cerebral blood flow. We also analyzed the role of CSF PDGFRβ in the relationship between aging, BBB dysfunction (measured by CSF/plasma albumin ratio, QAlb), and neuroinflammation (i.e., CSF levels of YKL-40 and glial fibrillary acidic protein [GFAP], preferentially expressed in reactive astrocytes). The cohort had a mean age of 67 years (CU = 62.8, MCI = 69.9, dementia = 70.4), and 50.1% were male (CU = 46.6%, MCI = 53.7%, dementia = 54.3%). Higher CSF PDGFRβ concentrations were related to higher age ( = 19.1, β = 0.5, 95% CI 16-22.2, < 0.001), increased CSF neuroinflammatory markers of glial activation YKL-40 ( = 3.4, β = 0.5, 95% CI 2.8-3.9, < 0.001), GFAP ( = 27.4, β = 0.4, 95% CI 20.9-33.9, < 0.001), and worse BBB integrity measured by QAlb ( = 37.4, β = 0.2, 95% CI 24.9-49.9, < 0.001). Age was also associated with worse BBB integrity, and this was partly mediated by PDGFRβ and neuroinflammatory markers (16%-33% of total effect). However, PDGFRβ showed no associations with ε4 genotype, PET imaging of Aβ and tau pathology, or MRI measures of brain atrophy and WMLs ( > 0.05). In summary, pericyte damage, reflected by CSF PDGFRβ, may be involved in age-related BBB disruption together with neuroinflammation, but is not related to Alzheimer-related pathologic changes.